CORRELATION OF CHOLESTEROL LEVELS AND BLOOD PRESSURE IN HYPERTENSION PATIENTS AT THE KIDNEY & HYPERTENSION POLYCLINIC, TABANAN HOSPITAL - Devy, Anggi Amanda Triana; Dewi, Ni Nyoman Ayu; Ruma, I Made Winarsa; Wihandani, Desak Made (E-Jurnal Medika Udayana, 2024)
Blood pressure can increase because the walls of blood vessels become narrow and stiff due to the accumulation of cholesterol in the body. This study aims to determine the correlation between blood pressure and cholesterol levels in hypertension patients. This study was a cross-sectional study from secondary data on hypertension patients at the Kidney & Hypertension Polyclinic at RSUD Tabanan who met the inclusion and exclusion criteria. The minimum sample size required is 51 people. Of the 51 research subjects, 26 people (51%) were women and 25 people (49%) were men, 19 patients (37,25%) had grade 1 hypertension and 32 patients (62,75%) had grade 2 hypertension. Total cholesterol and LDL levels were found to be significantly higher in patients with grade 2 hypertension compared to grade 1 hypertension with p<0,05. Pearson correlation analysis showed a correlation between total cholesterol levels and systolic blood pressure (r=0.456, p=0,001), but no correlation was found between total cholesterol levels and diastolic blood pressure (r=0.036, p=0,804). Meanwhile, Spearman correlation analysis showed a correlation between LDL cholesterol levels and systolic (r=0.414, p=0,003) and diastolic (r=0.428, p=0,002) blood pressure. The results of this study show that total cholesterol levels with systolic blood pressure and LDL cholesterol with systolic and diastolic blood pressure have a positive correlation with moderate strength. However, further research is needed with prospective methods to obtain a direct relationship between cholesterol levels and blood pressure. Keywords : Hypertension, Total cholesterol, LDL cholesterol